Diagnóstico de vida laboral en tres minas de carbón de la región de Samacá (2011)
This paper presents an assessment of the Quality of Working Life (QWL) in the mining sector of coal in three mines in the region of Samacá - Boyacá.An exploratory, descriptive research is applied, with probability sampling, a sample of 110 workers, to this purpose an evaluative instrument designed in this work is used and it consists of two parts: a survey from the Survey of Quality of Life at Work (SQLW) and an interview based on the dimensions isolated by Cantera, adapted to measure the QWL in the coal mining sector.Finally this article proposes a model based on the differentiated six essential factors after processing of data obtained in this study, to facilitate the sector’s organizations conducting improvement plans to seek a balance in the QWL of employees thus forging a winwin relationship between employee and employe